2000
DOI: 10.1063/1.127072
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic oscillations of red photoluminescence from nanocrystalline Si/SiO2 films

Abstract: Experimental investigations on the red photoluminescence (PL) from nanocrystalline Si (nc-Si) embedded in a SiO2 matrix, fabricated by plasma-enhanced chemical vapor deposition and a subsequent post-treatment, reveal under certain conditions the occurrence of kinetic oscillations. For the red PL between 1.5 and 1.75 eV, the spectral shift and the peak intensity versus annealing times show temporal oscillations. The spectral variations are explained by the growth and decay kinetics of two oxygen thermal donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Although the exact mechanism for light emission remains controversial, nowadays it is well established that basically it relies either on NC size effects [7][8][9] or on radiative processes at the Si NCs/matrix interface. [9][10][11][12] Several techniques have been used to produce Si NCs embedded in a SiO 2 matrix, among them chemical vapor deposition ͑CVD͒, molecular beam epitaxy ͑MBE͒, laser ablation, and in particular the ion implantation technique. This last one has been used quite frequently because it has several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism for light emission remains controversial, nowadays it is well established that basically it relies either on NC size effects [7][8][9] or on radiative processes at the Si NCs/matrix interface. [9][10][11][12] Several techniques have been used to produce Si NCs embedded in a SiO 2 matrix, among them chemical vapor deposition ͑CVD͒, molecular beam epitaxy ͑MBE͒, laser ablation, and in particular the ion implantation technique. This last one has been used quite frequently because it has several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…for the band centered on 780 nm. This behavio r is characteri stic o f PL emission produced by radiati ve sta tes at the Si/Si0 2 interfa ce as recogn ized previously by other a uthors [1, [8][9][10][11]. Therefore, we can conclude that both bands havc basically different origins, one band on qu anmm size effects and the other on radiative interface sta tes.…”
Section: Discussioumentioning
confidence: 50%
“…However, the peak energy of the PL spectra doesn't equal to the corresponding band gap obtained from the F-B optical dispersion model fitting. This implies that the luminescence band is not only affected by the QC effect but also some other factors such as defects at the nanocluster surface [29], excitation via the nanocluster-nanocluster surface [29], Si-Si bonds within the nanocluster itself [30] or oxide-related defect states [31]. Recent research have confirmed that both QC effect and kinds of defect are main factors impacting the PL spectra and the origin of PL can be shifted in a single sample by certain methods [32,33].…”
Section: Discussionmentioning
confidence: 98%